Emerging roles of long non-coding RNAs in keloids - Yu, Xin; Zhu, Xueqing; Xu, Hongjun; Li, Linfeng (Frontiers in Cell and Developmental Biology, 2022)
Keloids are pathologic wound healing conditions caused by fibroblast hyperproliferation and excess collagen deposition following skin injury or irritation, which significantly impact patients by causing psychosocial and functional distress. Extracellular matrix (ECM) deposition and human fibroblast proliferation represents the main pathophysiology of keloid. Long non-coding RNAs (LncRNAs) play important roles in many biological and pathological processes, including development, differentiation and carcinogenesis. Recently, accumulating evidences have demonstrated that deregulated lncRNAs contribute to keloids formation. The present review summarizes the researches of deregulated lncRNAs in keloid. Exploring lncRNA-based methods hold promise as new effective therapies against keloid.